Computer-based Decision Support in the Management of Primary Gastric non-Hodgkin Lymphoma - Lucas, P. J. F.; Boot, H.; Taal, B. G. (Methods of Information in Medicine, 1998)
Primary non-Hodgkin lymphoma of the stomach is a rare disorder for which clinical management has not yet been settled completely. Faced with the many uncertainties associated with the selection of a treatment for a patient with this disorder, it is difficult to determine the treatment that is optimal for the patient, as well as the prognosis to be expected. The development of a decision-theoretic model of non-Hodgkin lymphoma of the stomach is described. The model aims to assist the clinician in exploring various clinical questions, among others questions concerning prognosis and optimal treatment. Central to the model is a probabilistic network that offers an explicit representation of the uncertainties underlying the decision-making process. The model has been incorporated in a decisionsupport system. Preliminary evaluation results indicate that the performance ofthe model in its present form matches the performance of experienced clinicians.
Keywords: Medical Decision Making; Medical Expert Systems; Probabilistic Networks; Influence Diagrams; Gastric Lymphoma